THE VIOLATING MAXIMS OF MAIN CHARACTERS IN THE HANGOVER MOVIE’S SCRIPT - Nanda Chairunnisa; Muhammad Natsir (State University of Medan, 2014)
ABSTRACT The study deals with the types of maxims violation in The Hangover movie’s script used by the main characters. The objectives of study were to describe the violation of maxim, to describe the dominant type of maxim violation and to elaborate the reason for the maxim violation. The data were the dialogue of main characters in The Hangover movie. This research was conducted by using descriptive qualitative and limited on the main characters. The data analysis findingsshowthat there are 22 violation of maxim of quality, 2 violation of maxim of quantity, 9 violation of maxim of relation, and 8 violation of maxim of manner.The reason of the violations areto give the lack of evidence, to lying to other speaker in hiding the truth, to save face the embarrassment, to present the strongest information, to represent what is in the speaker’s mind, or to trick audience or listener for making a joke or not. Keyword : cooperative principle, violation of maxim, movie.